In vitro investigation of the antiviral activity of propolis and chitosan nanoparticles against the genotype VII Newcastle disease virus - Noura Alkhalefa; Samy Khaliel; Abdelnaby Tahoon; Hanan Shaban; Asmaa Magouz; Hanaa Ghabban; Maha S. Lokman; Maha S. Lokman; Ehab Kotb Elmahallawy (Frontiers in Veterinary Science, 2022)
The Newcastle disease virus (NDV) is considered a serious threat to global poultry production. Despite the availability of vaccines, it remains a major devastating epidemic responsible for great economic losses. The development of novel virus-controlling strategies is therefore an urgent need. The present study investigated for the first time the antiviral efficacy of propolis and chitosan nanoparticles against two NDV isolates, MW881875 and MW881876, recovered from vaccinated commercial broiler farms in KafrEl Sheikh Governorate, Egypt. The polygenetic analysis focused on the F and M genes, with one isolate having a 97% identity with the genotype VII NDV Israeli strain. On the other hand, the identified isolates showed high genetic variation and only 76% identity with the LaSota vaccine (genotype II). More interestingly, the cell cytotoxic concentrations of chitosan, propolis, and a propolis–chitosan mixture against Vero cells were 327.41 ± 12.63, 109.48 ± 8.36, and 231.78 ± 11.46 μg/ml, respectively. The median tissue culture infectious dose (TCID50) assay demonstrated that the nanoparticles have antiviral effects after NDV exposure resulting in significant decrease in viral titer (TCID50) by 2, 2.66, and 2.5 log10 at 62 μg/ml of chitosan, 13 μg/ml of propolis, and 30 μg/ml of the propolis–chitosan mixture, respectively, compared with the control TCID50 value of 4 log10. Taken together, the results provide novel insights into the potentially promising roles of propolis and chitosan as novel, safe, and effective antiviral agents against NDV.